Large Animal Surgery Supplemental Notes - Malone, Erin; Open Textbook Library (Open Textbook Library, 2019)
This textbook includes basic principles of large animal surgery and anesthesia, how to apply those principles to cases and situations, and discover ways of finding answers when you don't remember the information, are presented with cases that aren't "textbook" and/or things don't go as planned.
Introduction -- Finding Resources -- General Surgery -- General pharmacology -- Equine Drugs -- Food Animal Drugs -- Food Animal Drug Regulations -- Equine and Camelid Castration -- FA youngstock processing -- LA Respiratory Issues -- Eye surgery -- LA umbilical disorders -- Bladder, Urethra and Ureters -- Male urogenital surgery -- Female urogenital surgery -- Food/Fiber Cesarean Sections -- Large animal masses -- Large animal cutaneous neoplasia -- Large animal wounds -- Equine Oral, Esophageal and Rectal disorders -- Equine Colic -- FA GI Diagnostics & GI Surgery Principles -- FA GI Topics -- Equine Lameness -- Equine podiatry -- Equine joint disorders -- Equine tendons and ligaments -- Equine bone disorders -- Equine muscle trauma -- Bovine Lameness -- Swine, SRC and poultry lameness -- LA Orthopedic Emergencies -- Appendix
In English.
Description based on print resource
Keywords: Medicine -- Textbooks